Electrodeposited Co-Mn oxide composite electrodes for rechargeable Zn-air battery - Wong, Christelle Pau Ping; Yang, Thomas C.-K.; Chong, Siewhui; Juan, Joon Ching; Pan, Guan Ting; Huang, Chao Ming (Springer Verlag (Germany), 2019)
Porous manganese cobalt oxide (MCO) films were prepared directly on a conductive stainless steel (SS) mesh substrate via electrodeposition and an annealing treatment as composite air electrodes. The electrodeposition time ratio markedly influenced the surface morphological and electrochemical catalytic activities of MCO/SS electrodes. The sample 04 (− 0.8 V for 480 s followed by − 0.9 V for 240 s and annealed at 400 °C for 2 h) exhibited the highest reduction current among all electrodes. The electrochemical catalytic activity of the sample 04 as the air electrode for rechargeable zinc–air batteries was evaluated using galvanostatic charge and discharge cycling measurements in a solution of 6 M KOH. After 1000 cycles, sample 04 exhibited excellent cycling stability, with an overall potential gap of 0.75 V. The excellent performance of MCO/SS electrode in terms of stability and overall potential gap might be due to the ratio of Co oxide and Mn oxide, and its porous structure. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.